2022
DOI: 10.1186/s12879-022-07123-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cytomegalovirus disease and viral replication kinetics in seropositive liver transplant recipients managed under preemptive therapy in a tertiary-care center in Mexico City: a retrospective cohort study

Abstract: Background In the absence of an adequate prevention strategy, up to 20% of CMV IgG+ liver transplant recipients (LTR) will develop CMV disease. Despite improved reporting in CMV-DNAemia, there is no consensus as to what the ideal CMV-DNAemia cutoff for a successful preemptive strategy is. Each transplant centre establishes their own threshold. We aimed to determine the effectiveness of our preventive strategy in CMV IgG+ LTR, and evaluate CMV replication kinetics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…85 A similar study in Liver Transplant recipients demonstrated that viral load growth rate was faster and doubling time shorter in patients who developed CMV DNAemia of ≥4000 IU/mL. 86…”
Section: Management Of CMV Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…85 A similar study in Liver Transplant recipients demonstrated that viral load growth rate was faster and doubling time shorter in patients who developed CMV DNAemia of ≥4000 IU/mL. 86…”
Section: Management Of CMV Infectionmentioning
confidence: 97%
“…85 A similar study in Liver Transplant recipients demonstrated that viral load growth rate was faster and doubling time shorter in patients who developed CMV DNAemia of ≥4000 IU/mL. 86 Foscarnet and cidofovir are considered second-line antivirals given their toxicity profiles (mainly nephrotoxicity). Despite hesitancy, foscarnet may be safe to use with the proper precautions and monitoring.…”
Section: Continued Next Pagementioning
confidence: 99%
“…12 Higher viral load thresholds above 1000 IU/mL in plasma or whole blood for AVT initiation during PET in CMV R + LTRs may also be effective. [13][14][15] prophylaxis in CMV R + LTRs is the reduction in AVT exposure (and associated costs and toxicities), and PET has not been shown to significantly reduce the incidence of CMV disease compared to prophylaxis in CMV R + LTRs, in part because the cumulative incidence of CMV disease with 3 months of valganciclovir prophylaxis is relative low, at approximately 5%. 12,16…”
Section: Explorationmentioning
confidence: 99%
“…We have found that PET using a viral load threshold of ≥250 IU (international units)/mL in plasma to be effective for CMV disease prevention and avoids the need for any CMV AVT in approximately 75% of CMV R + patients 12 . Higher viral load thresholds above 1000 IU/mL in plasma or whole blood for AVT initiation during PET in CMV R + LTRs may also be effective 13–15 . Some centers may already incorporate different CMV preventive strategies for D + R − and R + populations, 6 and familiarity with serostatus‐guided practices may mitigate confusion surrounding serostatus‐guided AVT initiation thresholds.…”
Section: Approach To Implementation Of Pet In a Real‐world Settingmentioning
confidence: 99%
“…Monitoring as part of preemptive therapy is recommended at least once weekly for 3–4 months after kidney or liver transplantation and may be extended if there is an ongoing increased risk for HCMV disease [ 9 ]. Although there is no consensus for the optimal HMCV-DNAemia cut-off for initiating preemptive therapy, a recent retrospective study showed that using a threshold of ≥4000 IU/mL was effective in reducing the incidence of end-organ disease in R+ LiTR [ 24 ]. Thresholds for initiating preemptive therapy are usually defined on available assays and patient risk factors [ 9 ].…”
Section: Human Cytomegalovirusmentioning
confidence: 99%